LEGAL REVIEW OF CANCELLATION OF AGREEMENT BORROW FOR LAND ORDERLY - Muhammad Fadly; Mhd Syukran Yamin Lubis (Inspiring Law Journal, 2025)
This research is motivated by the position of the Curator who has the authority in the management and settlement of bankrupt assets, thus demanding independence as a fundamental principle to guarantee justice and protection of the interests of creditors and debtors. Article 15 paragraph (3) of Law Number 37 of 2004 concerning Bankruptcy and PKPU requires the Curator to be independent, honest, and impartial, but does not provide a clear definition or indicator regarding the phrase "independent". The ambiguity of this norm gives rise to different interpretations in practice and has implications for legal uncertainty and the potential for criminal liability of the Curator. Based on this, this research formulates problems regarding the regulation of the phrase "independent", the form of criminal liability of the Curator, and its implications for legal certainty. This research uses a normative legal research method with a statutory and conceptual approach. The legal materials used include primary, secondary, and tertiary legal materials, which are analyzed qualitatively to obtain a systematic and comprehensive legal understanding.and relevant to the research problem. The results of this study indicate that, first, the regulation of the phrase "independent" in Article 15 paragraph (3) of Law Number 37 of 2004 is a vague norm (vague norm) because it does not have a normative definition or objective indicators, so that its interpretation in practice becomes very objective. Second, the form of criminal liability of curators who are proven not to be independent is subject to general criminal law in Law Number 1 of 2023, which includes the offenses of embezzlement (Article 486), fraud (Article 492), and document falsification (Article 491), as long as the elements of actus reus and mens rea are proven. Third, the ambiguity of the phrase gives rise to legal implications in the form of significant legal uncertainty,For bankrupt debtors, this has the effect of hindering the process of settling bankrupt assets and delaying certainty about the legal status of assets, which prolongs the debtor's legal and economic burden. Furthermore, this situation raises the risk of excessive criminalization for curators and makes it difficult for commercial judges to provide objective assessments, ultimately undermining the credibility of the commercial justice system in Indonesia